Analisis Dampak Adanya Dewan Kawasan Aglomerasi dalam Undang-Undang Nomor 2 Tahun 2024 tentang Provinsi Daerah Khusus Jakarta terhadap Desentrlisasi Pemerintah Daerah - Scorpio, Belmondo; Nursadi, Harsanto (VISA: Journal of Vision and Ideas, 2025)
This research aims to find out what impacts arise and are felt as a result of the provision of an Agglomeration Area Council in the Special Region of Jakarta based on the instructions of Law Number 2 of 2024 concerning the Special Region of Jakarta Province on the decentralization of regional governments within the scope of the agglomeration area. This study is a literature review using normative juridical research methods. The results of the study found that the agglomeration area stipulated in Law Number 2/2024 is an area for synchronizing policies related to spatial development and regional development plans. The Agglomeration Zone Council itself has the authority to coordinate, monitor and evaluate the synchronization of regional development implementation. The authority of the Agglomeration Area Council does not take away the regional government's authority or decentralization and regional autonomy, but the agglomeration area program is still implemented by the regional government in accordance with its autonomy, while the Agglomeration Area Council only carries out synchronization and coordination. Therefore, the impact of the existence of the Agglomeration Area Council is only to align the work programs carried out by regional governments which are included in the scope of the Jabodetabekjur Agglomeration Area.